Conserved enhancer logic controls the notochord expression of vertebrate Brachyury - Kemmler, Cassie L; Smolikova, Jana; Moran, Hannah R; Mannion, Brandon J; Knapp, Dunja; Lim, Fabian; Czarkwiani, Anna; Hermosilla Aguayo, Viviana; Rapp, Vincent; Fitch, Olivia E; Bötschi, Seraina; Selleri, Licia; et al. (bioRxiv, 2023)
The cell type-specific expression of key transcription factors is central to development. Brachyury/T/TBXT is a major transcription factor for gastrulation, tailbud patterning, and notochord formation; however, how its expression is controlled in the mammalian notochord has remained elusive. Here, we identify the complement of notochord-specific enhancers in the mammalian Brachyury/T/TBXT gene. Using transgenic assays in zebrafish, axolotl, and mouse, we discover three Brachyury-controlling notochord enhancers T3, C, and I in human, mouse, and marsupial genomes. Acting as Brachyury-responsive, auto-regulatory shadow enhancers, deletion of all three enhancers in mouse abolishes Brachyury/T expression selectively in the notochord, causing specific trunk and neural tube defects without gastrulation or tailbud defects. Sequence and functional conservation of Brachyury-driving notochord enhancers with the brachyury/tbxtb loci from diverse lineages of fishes dates their origin to the last common ancestor of jawed vertebrates. Our data define the enhancers for Brachyury/T/TBXTB notochord expression as ancient mechanism in axis development.